[Image 60] - Smith, Captain Sir William [?ob. 1732] (My University, 1802)
Captain Sir William Smith was in the Royal Engineers.
Original drawings and paintings of Ireland and Scotland, vol 1
View of Carrickbrachy an old Irish foothill of the (improperly called) Isle of Doagh drawn as looking towards Dunnaff Head by Sir William Smith in 1802.
Keywords: Isle of Doagh; Carrickabrachy; Dunnaff; Fortification; Architectural drawings; Ireland -- Antiquities -- Pictorial works; Donegal (Ireland : County) -- Pictorial works; Inishowen Peninsula (Ireland) -- Pictorial works; Landscapes (Representations) 1800-1810